Programmable logic controller (PLC) - level 1 & 2 - Nik Anwar, Nik Syahrim (Penerbit UTeM Press, 2024)
This book covers advanced concepts and applications of Programmable Logic Controllers (PLCs) with a focus on OMRON systems. Chapter One introduces PLC fundamentals, historical background, system configuration, unit specifications, and advantages, as well as input and output device connections and wiring diagrams. Chapter Two explains basic programming using the CX-Programmer software, including I/O memory addressing and the development of holding circuits using internal relays and instructions such as KEEP, SET, and RSET.